Numerical model to simulate the forward and reverse sound transmission mechanism in hearing - González-Herrera, Antonio; Camacho, Javier; García-Manrique-Ocaña, José Manuel (My University, 2017)
The human hearing system captures acoustic waves in air that are transmitted to the cochlea where are converted in nerve signal. Meanwhile, at the cochlea, some sensory cell are active provoking sound transmission in the reverse direction. These called otoacoustic emissions are measured in the ear canal as diagnostic method. Forward and reverse transmission mechanisms are complex being a matter of research. Its study presents great difficulty, either by experimental or numerical methods. A simplified experiment has been designed to evaluate both mechanisms. It consists of a system with the basic elements (air, tympanic membrane and ossicular chain).The present paper presents results corresponding to a previous numerical study. Methodology is described, it is based in previous work. Main results are shown in terms of modal analysis and sound pressure fields. Comparing with the behavior of a membrane , the presence of the umbo adds stiffness and mass to the system. Results prove that the effect of the mass is more significant, increasing the number of modes present in the range of frequency of interest. Comparing forward and reverse mechanisms, the main difference is on the side of the stimuli, similar to the opposite side.
Keywords: Analizadores de sonido; Mechanic of hearing; sound transmision